The relationships between glucose variability and renal function in type 2 diabetes patients on basal-bolus insulin therapy - Vadim V. Klimontov; Natalia E. Myakina (Сахарный диабет, 2015)
Aim. To assess the relationship of glucose variability (GV) and renal function in patients with type 2 diabetes on basal-bolus insulin therapy.Materials and methods. We observed 101 females with type 2 diabetes, aged 47–79 years, with a glomerular filtration rate (GFR) >30 mL/min/1.73 m2. Insulin was combined with metformin in 45 of these women. The mean glucose and standard deviation, continuous overlapping net glucose action, lability index, J-index, low blood glucose index (LBGI), high blood glucose index (HBGI), M-value and mean absolute glucose (MAG) were calculated based on the results of blinded continuous glucose monitoring. The prevalence of episodes of low interstitial glucose (<3.9 and 2.8 mmol/L) of at least 20-min duration was estimated.Results. Patients with a GFR of 30–44 mL/min/1.73 m2 had significantly lower HBGI, J-index, MAG and M-value compared with those with better filtration (all p < 0.05); LBGI was not dependent on GFR. The GFR values were weakly and positively correlated with HBGI, J-index, M-value and MAG. Multiple regression analysis showed that GFR is an independent predictor of MAG (p = 0.04). No significant differences were found in the prevalence of episodes of low interstitial glucose between patients with different GFR ranges.Conclusions. GV parameters are related to renal function in type 2 diabetic women on basal-bolus insulin therapy. Patients with stage 3b chronic kidney disease have reduced GV, predominantly in the hyperglycaemic band, compared with those with better filtration.